In ovo delivery of carvacrol triggers expression of chemotactic factors, antimicrobial peptides and pro-inflammatory pathways in the yolk sac of broiler chicken embryos - Mila M. Y. Meijer; Henry van den Brand; Shahram Niknafs; Eugeni Roura (Journal of Animal Science and Biotechnology)
Abstract Background Broiler chickens are most vulnerable immediately after hatching due to their immature immune systems, making them susceptible to infectious diseases. The yolk plays an important role in early immune defence by showing relevant antioxidant and passive immunity capabilities during broiler embryonic development. The immunomodulatory effects of phytogenic compound carvacrol have been widely reported. After in ovo delivery in the amniotic fluid during embryonic development carvacrol is known to migrate to the yolk sac. However, it is unknown whether carvacrol in the yolk could enhance defence responsiveness in the yolk sac. Therefore, the aim of this study was to improve early immune function in chicken embryos, and it was hypothesized that in ovo delivery of carvacrol would result in immunomodulatory effects in the yolk sac, potentially improving post-hatch resilience. Methods On embryonic day (E)17.5, either a saline (control) or carvacrol solution was injected into the amniotic fluid. Yolk sac tissue samples were collected at E19.5, and transcriptomic analyses using RNA sequencing were performed, following functional enrichment analyses comparing the control (saline) and carvacrol-injected groups. Results The results showed that 268 genes were upregulated and 174 downregulated in the carvacrol group compared to the control (P < 0.05; logFC < −0.5 or log FC > 0.5). Functional analyses of these differentially expressed genes, using KEGG, REACTOME, and Gene Ontology databases, showed enrichment of several immune-related pathways. This included the pathways ‘Antimicrobial peptides’ (P = 0.001) and ‘Chemoattractant activity’ (P = 0.004), amongst others. Moreover, the ‘NOD-like receptor signaling’ pathway was enriched (P = 0.002). Antimicrobial peptides are part of the innate immune defence and are amongst the molecules produced after the nucleotide oligomerization domain (NOD)-like receptor pathway activation. While these responses may be associated with an inflammatory reaction to an exogenous threat, they could also indicate that in ovo delivery of carvacrol could prepare the newly hatched chick against bacterial pathogens by potentially promoting antimicrobial peptide production through activation of NOD-like receptor signaling in the yolk sac. Conclusion In conclusion, these findings suggest that in ovo delivery of carvacrol has the potential to enhance anti-pathogenic and pro-inflammatory responses in the yolk sac via upregulation of antimicrobial peptides, and NOD-like receptor pathways.